2023
DOI: 10.1080/07853890.2023.2233556
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided injection acupotomy as a minimally invasive intervention therapy for cervical spondylotic radiculopathy: a randomized control trial

Abstract: Objective To explore the efficacy and safety of ultrasound-guided injection acupotomy as a minimally invasive intervention treatment of cervical spondylotic radiculopathy (CSR). Methods 160 CSR subjects were recruited who met the inclusion criteria in our hospital from October 2019 to December 2021. The subjects were randomly divided into the experimental and control group, with 80 cases in each. The experimental group received ultrasound-guided injection acupotomy as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The needling depth may vary depending on gender, body mass index, and treatment area. The absence of navigational imaging devices may cause serious AEs [ 14 , 15 , 30 ]. Therefore, it is necessary to provide guidelines for safety procedures, including potential AEs based on individual patient characteristics, and procedural guidelines utilizing medical imaging devices, including safe needling depths [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needling depth may vary depending on gender, body mass index, and treatment area. The absence of navigational imaging devices may cause serious AEs [ 14 , 15 , 30 ]. Therefore, it is necessary to provide guidelines for safety procedures, including potential AEs based on individual patient characteristics, and procedural guidelines utilizing medical imaging devices, including safe needling depths [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have encompassed preliminary investigations into pre-procedural safety checks, procedural protocols, and infection prevention measures within the context of the acupotomy procedure, all aimed at fostering a secure environment and refining the acupotomy technique [ 11 , 12 , 13 ]. Furthermore, safety studies using medical imaging equipment such as ultrasound and magnetic resonance imaging have been actively conducted to determine safe needling depths for potentially risky acupuncture points [ 14 , 15 ]. A literature review identified real-world clinical side effects, offering accurate practitioner information [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of CS, Ns is used to remove the attached tissues. It protects the cervical intervertebral disc via adjustment of the mechanical features of the soft tissues around the cervical vertebra, relieving stress around the NP and delaying its degeneration [24][25][26]. Our previous study suggested that Ns therapy could inhibit IVDD by modulating the ECM collagen system and improving the altered structure of the NP [27].…”
Section: Introductionmentioning
confidence: 99%